2017
DOI: 10.1016/j.kjms.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of miR‐146a/b on the function of endothelial progenitor cells in acute ischemic stroke in mice

Abstract: The study aims to explore how microRNA-146a/b (miR-146a/b) regulates the function of endothelial progenitor cells (EPCs) in acute ischemic stroke in mice. Eighty male SPF C57BL/6J mice were evenly divided into the model-6 h, model-12 h, model-24 h (mice suffered from middle cerebral artery occlusion [MCAO] for 6 h, 12 h and model-24 h) and normal groups. EPCs were transfected and assigned into the control, MCAO, MCAO-miR-146a, MCAO-miR-146b and MCAO-miR-146a/b groups. The qRT-PCR was used to detect miR-146a/b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Despite the exact function of miRNA 146a downregulation during the acute phase of ischemic stroke is unclear, the previous work by Zhou et al26 demonstrated that the miRNA 146a downregulation has a protective effect on neural cells and it targeted pro-apoptotic genes to reduce apoptosis. Notably, a more recent report found that miRNA 146a/b significantly downregulated tumor necrosis factor receptor-associated factor 6 and IL-1 receptor-associated kinase 1 during the recovery phase of ischemic stroke, which in return favor the proliferation and migration of endothelial progenitor cells 27. miRNA 146a was found to enhance stroke-induced oligodendrogenesis as well 28.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the exact function of miRNA 146a downregulation during the acute phase of ischemic stroke is unclear, the previous work by Zhou et al26 demonstrated that the miRNA 146a downregulation has a protective effect on neural cells and it targeted pro-apoptotic genes to reduce apoptosis. Notably, a more recent report found that miRNA 146a/b significantly downregulated tumor necrosis factor receptor-associated factor 6 and IL-1 receptor-associated kinase 1 during the recovery phase of ischemic stroke, which in return favor the proliferation and migration of endothelial progenitor cells 27. miRNA 146a was found to enhance stroke-induced oligodendrogenesis as well 28.…”
Section: Discussionmentioning
confidence: 95%
“…Other examples of miRs thought to have important roles in mediating ischemic stroke outcomes include miR-146a/miR-146b [206], miR-9 [207], and miR-130b [208]. Upregulating the expression levels of miR-146a and miR-146b was shown to promote proliferation and angiogenesis of endothelial progenitor cells after acute ischemic stroke in mice [206].…”
Section: Mirs Involved In Telomere Shortening Cellular Senescencementioning
confidence: 99%
“…Other examples of miRs thought to have important roles in mediating ischemic stroke outcomes include miR-146a/miR-146b [206], miR-9 [207], and miR-130b [208]. Upregulating the expression levels of miR-146a and miR-146b was shown to promote proliferation and angiogenesis of endothelial progenitor cells after acute ischemic stroke in mice [206]. While not yet directly linked to stroke, miR-9 has been shown to enhance neural stem cell proliferation, as well as angiogenesis, which could potentially work to enhance post-stroke CNS repair [207].…”
Section: Mirs Involved In Telomere Shortening Cellular Senescencementioning
confidence: 99%
“…miR-21 mimics can increase integrity of CSCs and improve their proliferation and migration via the target PTEN [12]. Moreover, miR-146a is suggested to enhance migration, proliferation and angiogenesis ability of endothelial progenitor cells [55]. Notably, a single injection of miR-199a and miR-590 mimics immediately after MI in mice is sufficient to induce cardiomyocyte proliferation and promote stable recovery of cardiac function [20].…”
Section: Therapeutic Potential Of Mirnas In Heart Diseasementioning
confidence: 99%